DISEMINASI PENGETAHUAN TOKOH KI NARTOSABDHO MELALUI EVENT FESTIVAL SEABAD NADA DAN WARISAN KI NARTOSABDHO KEPADA PEGIAT SENI MAHASISWA DI KOTA SEMARANG SEBAGAI EVENT MANAGER, EVENT CONCEPTOR, EVENT EXECUTOR, PRODUCTION LOGISTICS, EVENT PRODUCTION GRAPHIC DESIGNER - Muhammad Raihan Tambunan; Yohanes Thianika Budiarsa (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2026)
This study examines the dissemination of knowledge about Ki Nartosabdho through thecultural event “Festival Seabad Nada dan Warisan Ki Nartosabdho” targeting student artcommunities in Semarang. The dominance of global popular culture has reduced youngpeople’s awareness of local cultural figures, requiring more relevant communicationapproaches. This research uses a qualitative approach with an implementation-based methodand the Integrated Marketing Communication (IMC) framework, integrating advertising,public relations, and experiential events. The findings show that the program increasedparticipation, knowledge, and cultural appreciation among participants. This study concludesthat cultural festivals with integrated communication strategies effectively bridge the gapbetween interest and understanding in cultural preservation.